On the Eastern Woman’s Body: Ethnic Stigma and Complex Trauma in Giuseppe Tornatore’s La sconosciuta (2006) - Haaland, Torunn (Quaderni d'Italianistica, 2022)
This essay discusses the construction of a post-traumatic subjectivity in Tornatore’s La sconosciuta. Following a sex-trafficking survivor’s struggle against ghosts of the past as well as present forms of offences and vulnerabilities, the narrative unfolds through flashbacks and dramatizations of the victim’s precariousness as an Eastern European, irregular, immigrant woman. The nexus that emerges between traumatization and stigmatization circles around the woman’s body and the contrast it personifies between her perceived cultural inferiority and physical desirability. Just as this character exposes the prejudice and discriminatory behaviour that perpetuate exclusion of ethnic minorities as well as systems and structures of injustice and exploitation, the ambivalences she embodies as a diligent and caring but also deceptive and violent nanny questions the victim/criminal paradigm typically present in public discourses concerning irregular immigrants and trafficking victims, especially. The critique of essentialist perceptions and practices merges with a focus on retraumatizing re-experiences that are triggered by sensory impressions and distressful interactions. Critical perspectives on complex trauma will illuminate possible correlations between the acute and protracted abuse represented and the susceptibility the character shows toward revictimization as well as the self-destructive and partly violent tendencies she exhibits. When she eventually starts to articulate past events and acquires a gradual control over her memories, it is largely for the presence of listeners who communicate empathy and detachment. Finally, it is this critical attitude that spectators are encouraged to assume to consider interconnections between essentialist exclusion, acute and protracted exploitation, and structures and systems of global injustice.